Does intellectual capital drive firm performance? Data from secondary sector companies on the Indonesia Stock Exchange - Akbar Syaifuddin As’ad; Rosinta Ria Panggabean (Jurnal Inovasi Ekonomi, 2021)
This research aims to determine the effects of Intellectual Capital, Leverage, and Liquidity on Firm Performance. Sample are secondary sector companies on the Indonesia Stock Exchange and used panel data regression for analysis; this research found that Intellectual Capital and Liquidity had a significant positive effect on Firm Performance, and Leverage did not have a considerable impact.